Achieving Adsorption of Cationic Dyes by the Composites Based on H3PMo12O40 Decorating Metal Organic Frameworks - Wenpeng Gong (Science Faculty of Chiang Mai University, 2019)
The novel H3PMo12O40/MOF-5(Zn4O(BDC)3) adsorbent has been prepared by hydrothermal synthetic method with H3PMo12O40 and metal-organic frameworks (MOF-5) as materials active species and supports, respectively. The composition, structure, morphology, stability and toleration of H3PMo12O40/MOF-5 have been characterized through X-ray powder diffraction pattern (XRD), Fourier transform infrared spectrum (FT-IR), scanning electron micrographs (SEM), thermogravimetric (TG), brunaue Emmett teller (BET). The adsorption of methylene blue onto H3PMo12O40/MOF-5 in aqueous solution was studied. The effects of the experimental parameters, including sample solution initial pH, temperature and initial concentration have been investigated. The results showed that the lower temperature and lower pH value were beneficial to the dye adsorption. The experiment data could be well described by the Langmuir equations and pseudo-sencond-order kinetic model. Thermodynamic parametars dG<0, dH<0 and dS>0 indicated that the MB adsorption onto H3PMo12O40/MOF-5 was spontaneous and endothermic, the adsorption towards methyl violet, rhodamine B and malachite green cationic dyes also showed good adsorption properties. The quite efficient adsorption of cationic dyes in aqueous solution on H3PMo12O40/MOF-5 was studied.